O estudo da cinemática vetorial por meio de um tutorial do software tracker. - Carvalho, Daiane Batista (2024)
Learning is the goal of teaching, even if it is not always achieved. For this reason, school education is essential for human development. It is noteworthy that, in this work, we do not seek the causes that make knowledge difficult or impossible, but propose a set of interventions that can influence student learning. One of the main difficulties in teaching Physics is the visualization of physical phenomena, since they depend a lot on the student's abstraction to be understood. As a counterpoint to this issue, computer applications present themselves as an efficient didactic tool, because their graphical and dynamic environments can attract the attention and help in the understanding of the contents, motivating the student in the search for knowledge. In this perspective, we decided to verify learning through a methodological approach to the study of motion vector kinematics, in this case, in the Oblique Launch, with the use of educational technologies in physics teaching. The methodological procedure adopted in this research consists in the construction of didactic sequences with a tutorial exemplifying the installation and handling of the Tracker software, including in the process the video analysis, data generation and simulations developed with the software. The study has as its principle the analysis of the video that records the physical phenomena, using the capture of movement frame by frame or frame by frame. The application of the didactic sequence was carried out in a 6th grade class. The process was efficient, had a good acceptance by the students, the tool provided autonomy, performance and also the first contact with experimentation by the students.